2023
DOI: 10.1186/s12889-023-16294-3
|View full text |Cite
|
Sign up to set email alerts
|

Do peer-based education interventions effectively improve vaccination acceptance? a systematic review

Abstract: Background Vaccination efforts are a vital part of controlling the spread of diseases, however, lack of vaccine acceptance undermines the efficacy of this public health effort. Current evidence suggests that the most effective interventions to support vaccination uptake and positive vaccination beliefs are multicomponent, and dialogue based. Peer-based education interventions are such a strategy that involves an individual within the same group to act as the vaccine educator. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The parallel mediation analysis results showed that, amongst the three vaccine confidence domains, vaccine importance was identified as the only significant mediator of the association between the pay-it-forward intervention and vaccine uptake, and confidence in safety and effectiveness were found to be less relevant to the mediation pathway in our study sample. Our interpretation is that, in the Chinese market where there is still limited awareness and demand for influenza vaccines, pay-it-forward approach as an intervention package containing educational, peer-based psycho-behavioral, and community engagement components may help enhance public awareness and trust, perceived vaccine importance and subsequent acceptance of the vaccine [36] , [37] , [38] . This is supported by previous pay-it-forward studies suggesting that positive experiences (e.g., kindness and reciprocity generated among the community through donations and handwritten messages) contributed to community solidarity, public trust and encouraged people to receive medical service [39] , [40] , [41] , [42] , [43] .…”
Section: Discussionmentioning
confidence: 99%
“…The parallel mediation analysis results showed that, amongst the three vaccine confidence domains, vaccine importance was identified as the only significant mediator of the association between the pay-it-forward intervention and vaccine uptake, and confidence in safety and effectiveness were found to be less relevant to the mediation pathway in our study sample. Our interpretation is that, in the Chinese market where there is still limited awareness and demand for influenza vaccines, pay-it-forward approach as an intervention package containing educational, peer-based psycho-behavioral, and community engagement components may help enhance public awareness and trust, perceived vaccine importance and subsequent acceptance of the vaccine [36] , [37] , [38] . This is supported by previous pay-it-forward studies suggesting that positive experiences (e.g., kindness and reciprocity generated among the community through donations and handwritten messages) contributed to community solidarity, public trust and encouraged people to receive medical service [39] , [40] , [41] , [42] , [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Educated mothers have greater access to healthcare services, sources of information that support vaccination, and knowledge of the advantages and risks of vaccine-preventable diseases. They may also be influenced by peer-based education interventions that use conversation and trust to encourage vaccination [50] , [51] .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reviews published or indexed after December 2022 evaluated vaccination uptake and barriers and facilitators to this in both general populations and minority or otherwise vulnerable groups in the context of COVID-19 vaccination programmes. However, only three reviews would have been eligible for inclusion in out review [ 38 40 ].…”
Section: Strengths and Limitations: Scope Of Reviewmentioning
confidence: 99%
“…One contained a single relevant RCT relating to willingness to receive COVID-19 vaccination among black and minority ethnic people in the UK and explored the effectiveness of exposure to different forms of written information [ 40 ]. Another contained two relevant RCTs targeting influenza vaccination in older adults with or without additional markers of vulnerability or marginalisation [ 38 ]. While we would include these reviews in an update of this overview we do not consider that they are likely to substantively change our findings.…”
Section: Strengths and Limitations: Scope Of Reviewmentioning
confidence: 99%